A novel bioorganic calcium enhancement for the germination and physical growth of fodder grass, Cenchrus ciliaris L. - Tareq, A M; Merlin, K D (Plant Science Today, 2026)
Global agricultural crop production relies on organic fertilisers for safer food production and ecosystem sustainability. Huge quantities of residues from eggs, the cases, are discarded day-to-day all around the world, posing a severe threat to the environment. The enormous wastage could be made beneficial to the plants as an effective calcium supplement. Cenchrus ciliaris L. is a perennial grass, cultivated for its palatable foliage as fodder. With an attempt to reuse the egg leftovers, a greenhouse experiment was conducted by utilising the powdered form of egg case as an organic fertiliser and a source of calcium to assess the germination potential and physical performance of C. ciliaris. Five diverse rates of the egg case powder, viz., 4, 8, 12, 16 and 20 g, were mixed with the potting mixture for the investigation. A chemical fertiliser, calcium nitrate and an organic chemical source, bone meal, were used for comparison along with an untreated control. The results revealed an outstanding germination potential and further plant physical growth with the egg cases acting as a calcium source for C. ciliaris plants. A hundred per cent germination and higher rates of growth parameters viz., leaf length, leaf breadth, leaf area, leaf production, shoot and root height were noticed in the highest dose investigated (20 g). The subsequent doses (16, 12 and 8 g) produced immense results as well. The fresh and dried biomass of C. ciliaris plants also yielded the highest amount for the highest dose of egg case-supplemented plants. The lowest dose (4 g) produced concordant results with the standard chemical fertiliser, calcium nitrate. Consequently, it is determined that calcium-rich egg cases can enhance the germination rates and physical performance of C. ciliaris plants.